The Influence of Work Culture and Communication on Public Reporting Quality via Qlue in Tanjung Duren - Syauqi, Ahmad (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
This study examines the influence of work culture and communication among public officials on the quality of public reporting services at the Head of the Subdistrict Office in Tanjung Duren, West Jakarta, with a specific focus on the implementation of the Qlue application. Using a descriptive quantitative research method, the study investigates two independent variables—work culture and communication—and their effects on the dependent variable, namely the quality of public reporting services. Data collection was carried out through a census technique involving 150 respondents. The findings show that work culture significantly influences the quality of public services, contributing 53.9% to the variance. Communication also has a significant effect, accounting for 54.5%. When both variables are combined, they explain 57.1% of the variance in the quality of public reporting services. These results indicate that improving both internal culture and communication practices among public officials can substantially enhance the effectiveness of digital public service platforms such as Qlue. The study emphasizes the importance of good leadership, effective policy implementation, and active community participation in optimizing service delivery. It is recommended that the Head of the Subdistrict Office take strategic steps to strengthen the work culture by improving officials’ attitudes, perspectives, and behaviors to maximize the potential of digital tools in public administration.